How to be a holist who rejects the biopsychosocial model - O'Leary, Diane (Array, 2021)
After nearly fifty years of mea culpas and explanatory additions, the biopsychosocial model is no closer to a life of its own. Bolton and Gillett give it a strong philosophical boost in The Biopsychosocial Model of Health and Disease, but they overlook the model"s deeply inconsistent position on dualism. Moreover, because metaphysical confusion has clinical ramifications in medicine, their solution sidesteps the model"s most pressing clinical faults. But the news is not all bad. We can maintain the merits of holism as we let go of the inchoate bag of platitudes that is the biopsychosocial model. We can accept holism as the metaphysical open door that it is, just a willingness to recognize the reality of human experience, and the sense in which that reality forces medicine to address biological, psychological, and social aspects of health. This allows us to finally characterize Engel"s driving idea in accurate philosophical terms, as acceptance of (phenomenal) consciousness in the context of medical science. This will not entirely pin down medicine"s stance on dualism, but it will position it clearly enough to readily improve patient care.